2013
DOI: 10.1111/ejn.12247
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive regulation of saccadic velocity by reward prospect

Abstract: It is known that expectation of reward speeds up saccades. Past studies have also shown the presence of a saccadic velocity bias in the orbit, resulting from a biomechanical regulation over varying eccentricities. Nevertheless, whether and how reward expectation interacts with the biomechanical regulation of saccadic velocities over varying eccentricities remains unknown. We addressed this question by conducting a visually guided double-step saccade task. The role of reward expectation was tested in monkeys pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 70 publications
(120 reference statements)
4
32
1
Order By: Relevance
“…These findings provide strong evidence for an effect of reward value on motor skill performance. Similar performance effects of reward have been shown in saccade velocity and wrist movement reaction times (Takikawa et al 2002;Xu-Wilson et al 2009;Opris et al 2011;Chen et al 2013). Accuracy of the movement, measured in success rate, also showed a significant effect of reward value, but aversive quinine-flavored pellets were accurately grasped by the end of training as well, indicating that grasps for quinine-flavored pellets were not invigorated but were still performed accurately.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These findings provide strong evidence for an effect of reward value on motor skill performance. Similar performance effects of reward have been shown in saccade velocity and wrist movement reaction times (Takikawa et al 2002;Xu-Wilson et al 2009;Opris et al 2011;Chen et al 2013). Accuracy of the movement, measured in success rate, also showed a significant effect of reward value, but aversive quinine-flavored pellets were accurately grasped by the end of training as well, indicating that grasps for quinine-flavored pellets were not invigorated but were still performed accurately.…”
Section: Discussionsupporting
confidence: 65%
“…Studies in rodents further supported this concept and showed that net expected rewards, rather than immediate reward history, determine performance vigor (Wang et al 2013). However, when the value of the upcoming reward was known beforehand, faster saccades were performed in high reward value trials compared with low reward value or no reward trials (Takikawa et al 2002;Xu-Wilson et al 2009;Shadmehr et al 2010;Chen et al 2013). Similar results were observed in an experiment studying reaction times of wrist movements (Opris et al 2011).…”
mentioning
confidence: 57%
“…Specifically, we tested for differences in latency and velocity of saccades, since previous studies have shown that expected reward can decrease the latency and increase the velocity of saccades (Kawagoe et al 1998;Haith et al 2012;Beierholm et al 2013;Choi et al 2014).…”
Section: Expected Reward Alters Saccade Latencies and Velocitiesmentioning
confidence: 99%
“…Therefore, to ask whether saccade velocity varies with reward expectancy, we needed a velocity measure that accounts for the fact that velocity varies as a function of amplitude. We use "vigor" (Choi et al 2014), which describes how much the velocity of a saccade is above or below the expected velocity (for all saccades) given the saccade amplitude (see METHODS for calculation of vigor; Fig. 2, F and G).…”
Section: Expected Reward Alters Saccade Latencies and Velocitiesmentioning
confidence: 99%
See 1 more Smart Citation